An Integrated Approach to Management of Short Stature in Children: Review Article - Bajracharya, Luna (Journal of Diabetes and Endocrinology Association of Nepal, 2020)
Short stature in children is a very common condition that requires timely investigations and management. Although there has been dramatic reduction in stunted growth in children below the age of 5 years during the last two decades in Nepal, the process of systemic screening and evaluation followed by timely treatment can still be made better. Awareness programs for short stature such as at the time of birth of baby and use of social media for its dissemination in public can enhance short stature screening programs in schools, local ward clinics and other child health welfare programs as immunization. Children with suspected short stature can then further be referred to higher health centers as per need for investigations and management. Data generated may then be later used to develop algorithms and plan strategies to incorporate height well being in child healthcare policies. An integrated approach is necessary for maximum benefit.